Bioactive Polysaccharides from Marine Algae - Imarai-Bahamonde, C; Valenzuela-Montenegro, B (Elsevier Ltd, 2014)
Laminaran, fucoidan and sulfated galactan were extracted from the seaweeds Desmarestia distans, Lessonia vadosa, and Gigartina skottsbergii, respectively. Modified polysaccharides were prepared by desulfation, depolymerization, and sulfation. Antioxidant, anticoagulant and immunostimulating activities of native and modified polysaccharides were assayed in vitro. The oversulfated derivatives showed high antioxidant capacity towards oxygen radical assay; however, no direct relation between sulfate content and antioxidant capacity was found. Oversulfated polysaccharides presented higher antioxidant capacity towards hydroxyl radicals than the native polysaccharide. Regarding the ABTS•+radical cation assay moderate inhibition values (35.1-3.4%) were observed. The anticoagulant activity of native and modified polysaccharides was measured using the activated partial thromboplastin time assay; the native sulfated galactan from G. skottsbergii presented the highest value, close to that shown by heparin at similar concentrations. The immunostimulating activity of polysaccharides was measured through their effects on bone marrow-derived mice dendritic cell maturation. The native sulfated galactan from G. skottsbergii presented good dose-dependent activity inducing increased levels of MHC class II in dendritic cells. © 2014 Elsevier Ltd.